Improvement of power swing blocking scheme in distance protection relay - Ya'u, Mohammed Sani (2015)
Distance relay is a protective device in electrical power system. It detects faults in transmission system and isolates abnormal or fault conditions by sending a trip signals to the circuit breaker. Power swing is caused by the large disturbances in the power system that if not blocked, could cause wrong operation of the distance relay and can generate wrong or undesired tripping of the transmission line circuit breaker. Due to the characteristics of distance relay that can trip during power swings, a Power Swing Blocking (PSB) unit is developed to prevent unwanted distance relay operation during power swings. The main purpose of the PSB unit is to differentiate between faults and power swings and block distance or other relay elements from operating during a power swing. The problem with the originally available PSB in PSCAD/EMTDC is that it does not follow the exact shape of the operation characteristics of the available quadrilateral distance relay element. The PSB band may get too close to maximum load region, thus making load encroachment possible. This can create false fault or power swing pick up. Power swing blocking must be an immediate decision, immediately before allowing or disallowing the distance relay operations. Thus, PSB band must be attached back-to-back to the characteristic of the distance relay. Otherwise there will be an inaccuracy in measurement of impedance trajectory time interval from outer boundary to the inner boundary of the PSB band. This is the main problem when dealing with the current original PSB element in PSCAD/EMTDC. Therefore an improvement must be made to improve the power swing detection and thus make the quadrilateral distance relay element in the PSCAD/EMTDC to operate more efficiently. This improvement strategy will involve modelling an improved version of the original PSB and also introducing a new phasor comparator PSB scheme. These two techniques shall provide results that can validate the anticipated improvement in power swing detection over the original algorithm inherent in PSCAD/EMTDC. The original PSB problems are addressed in the newly improved FORTRAN and phasor comparator PSB schemes proposed in this research. In the original PSB available in PSCAD, the power swing detection time is close to the distance relay pick up time with a difference of only 0.01 second. This may cause wrong operation of distance relay if the relay picks up earlier and subsequently leading to a tripping of transmission line circuit breaker. However, the short seperation between the original PSB and the distance relay is addressed using the improved and phasor comparator PSB created in this research. In both cases, power swing detection is improved by 0.04 seconds. That gives sufficient time interval (0.04 seconds) between the PSB detection time and distance relay pick up time thus preventing the distance relay from sending a wrong tripping signal to the circuit breaker. With the modified PSB in the PSCAD/EMTDC, the problems related to the unmatched shapes of the PSB band and the quadrilateral distance relay operation characteristics have been addressed successfully.